Nano-diamond compact as well as preparation method and application thereof
By ball milling and mixing diamond powder and other materials, and performing reduction reactions and high-temperature and high-pressure treatment, nanodiamond composite sheets are formed, which solves the cracking problem of diamond composite sheets when synthesizing fine particles and improves the toughness and strength of the material.
Patent Information
- Application Number
- CN202311302983.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-10
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2043-10-10
AI Technical Summary
Diamond composite sheets have hard and brittle cracking problems when synthesizing fine particles. The material has high stress and high brittleness and is prone to cracking.
By mixing diamond micro powder, cubic boron nitride, tungsten carbide, cobalt powder, tantalum powder, vanadium powder and graphene ball mill, performing reduction reaction and pressing with cemented carbide sheets, heating and purifying and shaping under vacuum conditions, and finally processing under high temperature and high pressure to form a nanodiamond composite sheet.
It effectively prevents cracking of nanostructured diamond composite sheets, improves the toughness and strength of the material, and enhances the performance of nanodiamond composite sheets.
Smart Images

Figure CN119795680A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of diamond composite sheets, and in particular to a nano-diamond composite sheet and a preparation method and application thereof. Background Art
[0002] Diamond composite sheet is a superhard material composite sheet, which is mainly composed of diamond and polymerized on the surface of cemented carbide substrate. It has the characteristics of high hardness and good wear resistance. It is widely used in industries such as oil drilling, geological exploration, coal drilling and mining drill bits and mechanical processing tools, including commonly used machine tool turning tools, machining drill bits, frame processing milling cutters and copy milling cutters. Affected by processing needs, the precision requirements of workpieces are getting higher and higher, and the demand for superhard material tools is also getting higher and higher. Generally speaking, the finer the particle size of the diamond in the superhard material composite sheet, the smaller the surface roughness of the workpiece processed as a tool material, and the more it can meet the purpose of cutting instead of grinding in the non-ferrous metal or inorganic material processing industry, thereby saving the processing industry's requirements for high precision and processing efficiency, and reducing the time cost and labor cost of processing.
[0003] At present, the synthesis of diamond composite sheets mainly uses three black metal catalysts, iron, cobalt and nickel, to transform diamond particles into polycrystals through high temperature and high pressure. However, as the size of diamond particles decreases, the hardness and brittleness cracking problem of diamond composite sheets becomes more serious. The main problem with synthesizing fine-grained diamond composite sheets is that the material has high stress and brittleness, and is extremely easy to crack. Summary of the invention
[0004] In view of this, the object of the present invention is to provide a nano-diamond composite sheet and a preparation method and application thereof. The nano-diamond composite sheet provided by the present invention can effectively prevent the nano-structured diamond composite sheet from cracking.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a nano-diamond composite sheet, comprising a cemented carbide substrate and a superhard material hot-pressed on the surface of the cemented carbide substrate, wherein the superhard material is prepared from raw materials having the following mass percentages:
[0007]
[0008]
[0009] Preferably, the particle size of the diamond powder is 1 to 200 nm;
[0010] The diameter of the cubic boron nitride sheet is 1 to 100 nm;
[0011] The particle size of the tungsten carbide is 1 to 100 nm;
[0012] The particle size of the cobalt powder is 1 to 100 nm;
[0013] The particle size of the tantalum powder is 1 to 100 nm;
[0014] The particle size of the vanadium powder is 1-100 nm.
[0015] Preferably, the graphene is one or more of single-layer graphene, multi-layer graphene and graphene-like.
[0016] The present invention provides a method for preparing the above-mentioned nano-diamond composite sheet, comprising the following steps:
[0017] Diamond micropowder, cubic boron nitride, tungsten carbide, cobalt powder, tantalum powder, vanadium powder and graphene are ball-milled and mixed to obtain mixed micropowder;
[0018] placing the mixed micropowder in a hydrogen atmosphere to perform a reduction reaction to obtain reduced mixed micropowder;
[0019] Pressing the cemented carbide sheet and the reduced mixed micro powder into a pre-assembled composite sheet;
[0020] Under vacuum conditions, the pre-assembled composite sheet is heated, purified and shaped to obtain a purified and shaped composite sheet;
[0021] The purified and shaped composite sheet is subjected to high temperature and high pressure treatment to obtain a nano-diamond composite sheet.
[0022] Preferably, the ball milling mixing rate is 120-180 r / min, and the time is 3-9 h.
[0023] Preferably, the temperature of the reduction reaction is 350-950° C., and the time is 0.5-3 h; and the pressure of hydrogen in the hydrogen atmosphere is 0.02-0.1 MPa.
[0024] Preferably, the pressing pressure is 3 to 5 tons and the time is 3 to 30 seconds.
[0025] Preferably, the temperature of the heating, purification and shaping is 600-1100°C, and the holding time is 1-3h;
[0026] The vacuum degree of the vacuum condition is 10 -2 ~10 -4 Pa.
[0027] Preferably, the temperature of the high temperature and high pressure treatment is 1600-1900° C., the pressure is 5-6.5 GPa, and the heat and pressure holding time is 12-25 min.
[0028] The present invention provides application of the nano-diamond composite sheet in cutting tools.
[0029] The invention provides a nano-diamond composite sheet, comprising a cemented carbide substrate and a superhard material hot-pressed on the surface of the cemented carbide substrate, wherein the superhard material is prepared from raw materials comprising the following mass percentages: 85-95.5% of diamond micropowder; 1.5-6% of cubic boron nitride; 1-3% of tungsten carbide; 1-5% of cobalt powder; 0.5-3% of tantalum powder; 0.2-3% of vanadium powder; and 0.1-1% of graphene. The present invention adds cubic boron nitride, tungsten carbide and graphene, wherein the role of cubic boron nitride and tungsten carbide is to fill the diamond gap and form a bond with cobalt, tantalum and vanadium, preventing diamond from growing and reducing material stress, so that the material toughness increases; the graphene sheet structure can be converted into diamond during the diamond polycrystallization synthesis process so that there are more DD bonds between the two diamonds adjacent to the graphene, increasing the strength and toughness of the material, thereby being able to play a role in toughening and strengthening the nano-diamond composite sheet; in the present invention, cobalt powder, tantalum powder and vanadium powder play a role in catalytic bonding, and compared with iron powder and cobalt powder, the cobalt powder, tantalum powder and vanadium powder used in the present invention are more stable during use, less likely to be oxidized, and more suitable for the application of nano-level diamond composite sheet catalysts and adhesives. The nano-diamond composite sheet obtained by the present invention has good toughness and can effectively avoid the cracking of the nano-structured diamond composite sheet.
[0030] The present invention provides a method for preparing the nano-diamond composite sheet. During the high temperature and high pressure treatment, the diamond powder forms polycrystals, and DD bonds are formed between the diamond powder particles, so that the diamond particles are connected into sheets. The preparation method provided by the present invention is simple to operate and easy to realize industrial mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a microstructure diagram of the nano-diamond composite sheet obtained in Example 1. DETAILED DESCRIPTION
[0032] The present invention provides a nano-diamond composite sheet, comprising a cemented carbide substrate and a superhard material hot-pressed on the surface of the cemented carbide substrate, wherein the superhard material is prepared from raw materials having the following mass percentages:
[0033]
[0034]
[0035] Unless otherwise specified, the raw materials used in the present invention are all commercially available.
[0036] In the present invention, the cemented carbide is preferably YG16. In the present invention, the thickness of the cemented carbide is preferably 3 to 6 mm, more preferably 4 to 5 mm, and further preferably 3.5 mm.
[0037] In the present invention, the thickness of the superhard material on the surface of the cemented carbide is preferably 0.3-0.9 mm, more preferably 0.6 mm.
[0038] In terms of mass percentage, the superhard material comprises 85-95.5% diamond powder, preferably 88-92%, and more preferably 90%. In the present invention, the particle size of the diamond powder is preferably 1-200nm, more preferably 10-150nm, and more preferably 50-100nm.
[0039] In terms of mass percentage, the superhard material comprises 1.5-6% cubic boron nitride, preferably 2-5%, and more preferably 3-4%. In the present invention, the size of the cubic boron nitride is preferably 1-100 nm, more preferably 10-80 nm, and more preferably 30-50 nm.
[0040] In terms of mass percentage, the superhard material comprises 1-3% tungsten carbide, preferably 1.5-2.5%, more preferably 2%. In the present invention, the particle size of the tungsten carbide is preferably 1-100 nm, more preferably 10-80 nm, and further preferably 30-50 nm.
[0041] In terms of mass percentage, the superhard material comprises 1-5% cobalt powder, preferably 2-4%, more preferably 3%. In the present invention, the particle size of the cobalt powder is preferably 1-100 nm, more preferably 10-80 nm, and further preferably 30-50 nm.
[0042] In terms of mass percentage, the superhard material comprises 0.5-3% tantalum powder, preferably 1-2.5%, more preferably 1.5-2%. In the present invention, the particle size of the tantalum powder is preferably 1-100 nm, more preferably 10-80 nm, and further preferably 30-50 nm.
[0043] In terms of mass percentage, the superhard material comprises 0.2-3% vanadium powder, preferably 0.5-2.5%, more preferably 1-2%. In the present invention, the particle size of the vanadium powder is preferably 1-100 nm, more preferably 10-80 nm, and further preferably 30-50 nm.
[0044] In terms of mass percentage, the superhard material includes 0.1-1% graphene, preferably 0.3-0.8%, and more preferably 0.5%. In the present invention, the graphene is one or more of single-layer graphene, multi-layer graphene, and graphene-like. In the present invention, the number of layers of the graphene is preferably 1-20 layers, and more preferably 3-10 layers.
[0045] The present invention provides a method for preparing the above-mentioned nano-diamond composite sheet, comprising the following steps:
[0046] Diamond micropowder, cubic boron nitride, tungsten carbide, cobalt powder, tantalum powder, vanadium powder and graphene are ball-milled and mixed to obtain mixed micropowder;
[0047] placing the mixed micropowder in a hydrogen atmosphere to perform a reduction reaction to obtain reduced mixed micropowder;
[0048] Pressing the cemented carbide sheet and the reduced mixed micro powder into a pre-assembled composite sheet;
[0049] Under vacuum conditions, the pre-assembled composite sheet is heated, purified and shaped to obtain a purified and shaped composite sheet;
[0050] The purified and shaped composite sheet is subjected to high temperature and high pressure treatment to obtain a nano-diamond composite sheet.
[0051] The present invention ball-mills diamond micropowder, cubic boron nitride, tungsten carbide, cobalt powder, tantalum powder, vanadium powder and graphene to obtain mixed micropowder. In the present invention, the ball milling is preferably wet ball milling; the ball milling medium of the ball milling mixture is preferably stainless steel balls, and the dispersion medium is preferably an organic solvent, and the organic solvent is preferably one or more of ethanol, ethylene glycol, propanol, acetone and n-heptane, and more preferably ethanol.
[0052] In the present invention, the ball milling mixing rate is preferably 120 to 180 r / min, more preferably 120 to 150 r / min, and the time is preferably 3 to 9 h, more preferably 6 h.
[0053] In the present invention, after the ball milling, the obtained mixed micro powder is preferably dried and sieved. In the present invention, the drying temperature is preferably 80°C; and the sieving is preferably through a 100 mesh sieve.
[0054] After obtaining the mixed micropowder, the present invention places the mixed micropowder in a hydrogen atmosphere to perform a reduction reaction to obtain a reduced mixed micropowder. In the present invention, the pressure of hydrogen in the hydrogen atmosphere is preferably 0.02 to 0.1 MPa, and more preferably 0.04 to 0.08 MPa. In the present invention, the temperature of the reduction reaction is preferably 350 to 950°C, and more preferably 500 to 700°C; the time is preferably 0.5 to 3h, and more preferably 2h. In the present invention, metal powder is easily oxidized to oxides, thereby reducing the catalyst activity. The present invention can reduce the oxidized metal catalyst through the reduction reaction, thereby catalytic activity.
[0055] After obtaining the reduced mixed micropowder, the present invention presses the cemented carbide sheet and the reduced mixed micropowder to obtain a pre-assembled composite sheet. In the present invention, the press molding is preferably performed in a niobium cup. Specifically, the present invention preferably spreads the reduced mixed micropowder in the niobium cup, covers it with a cemented carbide sheet, matches a suitable molybdenum cup as a lid, and presses it. In the present invention, based on a niobium cup with a diameter of 35 mm, the mass of the reduced mixed micropowder used for a single press molding is preferably 3 to 5 g, and more preferably 3.5 g.
[0056] The present invention preferably uses a hydraulic press to perform the compression molding. In the present invention, the compression molding pressure is preferably 3 to 5 tons, more preferably 5 tons; the time is preferably 3 to 30 seconds, more preferably 5 to 20 seconds. In the present invention, the compression molding is preferably performed indoors at room temperature and a humidity of less than 45%.
[0057] After obtaining the pre-assembled composite sheet, the present invention heats and purifies the pre-assembled composite sheet under vacuum conditions to obtain a purified and shaped composite sheet. The present invention preferably performs the heating and purification in a vacuum furnace. In the present invention, the vacuum degree of the vacuum condition is preferably 10 -2 ~10 -4 Pa, more preferably 10 -4 Pa. In the present invention, the temperature of the heating purification and shaping is preferably 600-1100°C, more preferably 600-800°C; the holding time is preferably 1-3h, more preferably 2h. In the present invention, the heating rate to the heating purification and shaping temperature is preferably 20°C / min. In the present invention, during the heating purification process, the air adsorbed in the powder is released under vacuum and high temperature, and the adhesive is slightly melted at high temperature to change the material from powder to block and shape.
[0058] After obtaining the purified and shaped composite sheet, the present invention performs high temperature and high pressure treatment on the purified and shaped composite sheet to obtain a nano-diamond composite sheet. The present invention preferably performs the high temperature and high pressure treatment on a six-sided top press. In the present invention, the temperature of the high temperature and high pressure treatment is preferably 1600-1900°C, more preferably 1750-1800°C; the pressure is preferably 5-6.5GPa, more preferably 6GPa; the heat preservation and pressure holding time is preferably 12-25min, more preferably 18-20min. In the present invention, the heating rate of the high temperature and high pressure treatment is preferably 400°C / min, and the pressure increase rate is preferably 10GPa / min. In the present invention, during the high temperature and high pressure treatment, the diamond powder forms polycrystals, and DD bonds are formed between the diamond powder particles, so that the diamond particles are connected into sheets.
[0059] The present invention provides the use of the nano-diamond composite sheet in a tool. In the present invention, the tool is preferably one or more of a machining tool, an integral diamond milling cutter, an integral diamond drill bit, a micro-drill bit and a twist milling cutter.
[0060] The nano-diamond composite sheet and its preparation method and application provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0061] Example 1
[0062] (1) 93.0 g of 200 nm diamond powder, 2.0 g of 100 nm cubic boron nitride, 1.5 g of 1-100 nm tungsten carbide, 0.2 g of 3-10 layers of graphene, 2.0 g of 100 nm cobalt powder, 0.8 g of 200 nm tantalum powder, and 0.4 g of 1-100 nm vanadium powder were ball-milled in a stainless steel tank containing an organic solvent at a rate of 120 r / min for 6 hours. The mixture was dried at 80° C. and sieved through a 100-mesh sieve to obtain a mixed powder.
[0063] (2) The mixed micropowder is reduced in hydrogen at 500° C. for 2 h with a hydrogen pressure of 0.08 MPa to obtain reduced mixed micropowder.
[0064] (3) 3.5 g of reduced mixed micro powder was spread evenly into a niobium cup with a diameter of 35 mm and covered with a 3 mm thick cemented carbide (grade YG16). A suitable molybdenum cup was matched as a lid. The powder was compacted using a hydraulic press with a pressure of 5 tons to obtain a pre-assembled composite sheet.
[0065] (4) Place the pre-assembled composite sheet into a vacuum furnace and heat it for 10 -4 The purified and shaped composite sheet was obtained by heating at 600°C in vacuum and keeping the temperature for 2 hours.
[0066] (5) The purified and shaped composite sheet was matched with a conventional suitable carbon salt tube and pyrophyllite block, and subjected to high temperature and high pressure treatment in a six-sided top press, with a pressure of 6.0 GPa, a temperature of 1750° C., and a heat preservation and pressure holding time of 18 min to obtain a nano-diamond composite sheet with no cracks in appearance.
[0067] The microstructure of the obtained nano-diamond composite sheet is shown in Figure 1 As shown by Figure 1 It can be seen that the main material in black is nanodiamond with poor conductivity, the whiter material in the gaps between nanodiamonds is a cobalt-tantalum-vanadium mixture with better conductivity, and the gray material in the gaps is cubic boron nitride or tungsten carbide. The particles in the picture are connected to each other.
[0068] The wear ratio of the obtained nano-diamond composite sheet was tested using "JB / T 3235-2013: Determination of wear ratio of polycrystalline diamond". The wear ratio of the nano-diamond composite sheet obtained by the silicon carbide grinding wheel test was 1.8×10 4 .
[0069] The impact toughness of the obtained nano-diamond composite sheet was tested using an impact toughness testing machine. The nano-diamond composite sheet was processed by electric spark wire cutting into a sample with a diameter of 13.8 mm. The weight height was 13.5 cm, the weight was 0.6 kg, the single impact energy was 0.7938 J, and after 30 continuous impacts, the edge damage length was 1.65 mm, showing a dimple fracture.
[0070] Example 2
[0071] (1) 93.0 g of 200 nm diamond powder, 1.0 g of 100 nm cubic boron nitride, 2.5 g of 1-100 nm tungsten carbide, 0.2 g of 3-10 layers of graphene, 2.0 g of 100 nm cobalt powder, 0.8 g of 200 nm tantalum powder, and 0.4 g of 1-100 nm vanadium powder were ball-milled in a stainless steel tank containing an organic solvent at a rate of 120 r / min for 6 hours. The mixture was dried at 80° C. and sieved through a 100-mesh sieve to obtain a mixed powder.
[0072] (2) The mixed micropowder is reduced in hydrogen at 500° C. for 2 h with a hydrogen pressure of 0.08 MPa to obtain reduced mixed micropowder.
[0073] (3) 3.5 g of reduced mixed micro powder was spread evenly into a niobium cup with a diameter of 35 mm and covered with a 3 mm thick cemented carbide (grade YG16). A suitable molybdenum cup was matched as a lid. The powder was compacted using a hydraulic press with a pressure of 5 tons to obtain a pre-assembled composite sheet.
[0074] (4) Place the pre-assembled composite sheet into a vacuum furnace and heat it for 10 -4 The purified and shaped composite sheet was obtained by heating at 600°C in vacuum and keeping the temperature for 2 hours.
[0075] (5) The purified and shaped composite sheet was matched with a conventional suitable carbon salt tube and pyrophyllite block, and subjected to high temperature and high pressure treatment in a six-sided top press, with a pressure of 6.0 GPa, a temperature of 1750° C., and a heat preservation and pressure holding time of 18 min to obtain a nano-diamond composite sheet with no cracks in appearance.
[0076] The wear ratio of the obtained nano-diamond composite sheet was tested using "JB / T 3235-2013: Determination of Wear Ratio of Polycrystalline Diamond". The wear ratio of the nano-diamond composite sheet obtained by the silicon carbide grinding wheel test was 1.7×10 4 .
[0077] The impact toughness of the obtained nano-diamond composite sheet was tested using an impact toughness testing machine. The nano-diamond composite sheet was processed by electric spark wire cutting into a sample with a diameter of 13.8 mm. The weight height was 13.5 cm, the weight was 0.6 kg, the single impact energy was 0.7938 J, and after 30 continuous impacts, the edge damage length was 1.52 mm, showing a dimple fracture.
[0078] Example 3
[0079] (1) 94.0 g of 200 nm diamond powder, 1.0 g of 100 nm cubic boron nitride, 1.5 g of 1-100 nm tungsten carbide, 0.2 g of 3-10 layers of graphene, 2.0 g of 100 nm cobalt powder, 0.8 g of 200 nm tantalum powder, and 0.4 g of 1-100 nm vanadium powder were ball-milled in a stainless steel tank containing an organic solvent at a rate of 120 r / min for 6 hours. The mixture was dried at 80° C. and sieved through a 100-mesh sieve to obtain a mixed powder.
[0080] (2) The mixed micropowder is reduced in hydrogen at 500° C. for 2 h with a hydrogen pressure of 0.08 MPa to obtain reduced mixed micropowder.
[0081] (3) 3.5 g of reduced mixed micro powder was spread evenly into a niobium cup with a diameter of 35 mm and covered with a 3 mm thick cemented carbide (grade YG16). A suitable molybdenum cup was matched as a lid. The powder was compacted using a hydraulic press with a pressure of 5 tons to obtain a pre-assembled composite sheet.
[0082] (4) Place the pre-assembled composite sheet into a vacuum furnace and heat it for 10 -4 The purified and shaped composite sheet was obtained by heating at 600°C in vacuum and keeping the temperature for 2 hours.
[0083] (5) The purified and shaped composite sheet was matched with a conventional suitable carbon salt tube and pyrophyllite block, and subjected to high temperature and high pressure treatment in a six-sided top press, with a pressure of 6.0 GPa, a temperature of 1750° C., and a heat preservation and pressure holding time of 18 min to obtain a nano-diamond composite sheet with no cracks in appearance.
[0084] The wear ratio of the obtained nano-diamond composite sheet was tested using "JB / T 3235-2013: Determination of wear ratio of polycrystalline diamond". The wear ratio of the nano-diamond composite sheet obtained by the silicon carbide grinding wheel test was 1.8×10 4 .
[0085] The impact toughness of the obtained nano-diamond composite sheet was tested using an impact toughness testing machine. The nano-diamond composite sheet was processed by electric spark wire cutting into a sample with a diameter of 13.8 mm. The weight height was 13.5 cm, the weight was 0.6 kg, the single impact energy was 0.7938 J, and after 30 continuous impacts, the edge damage length was 1.68 mm, showing a dimple fracture.
[0086] Example 4
[0087] (1) 94.0 g of 200 nm diamond powder, 1.0 g of 100 nm cubic boron nitride, 1.5 g of 1-100 nm tungsten carbide, 0.2 g of 3-10 layers of graphene, 2.0 g of 100 nm cobalt powder, 0.8 g of 200 nm tantalum powder, and 0.4 g of 1-100 nm vanadium powder were ball-milled in a stainless steel tank containing an organic solvent at a rate of 120 r / min for 6 hours. The mixture was dried at 80° C. and sieved through a 100-mesh sieve to obtain a mixed powder.
[0088] (2) The mixed micropowder is reduced in hydrogen at 500° C. for 2 h with a hydrogen pressure of 0.08 MPa to obtain reduced mixed micropowder.
[0089] (3) 3.5 g of reduced mixed micro powder was spread evenly into a niobium cup with a diameter of 35 mm and covered with a 3 mm thick cemented carbide (grade YG16). A suitable molybdenum cup was matched as a lid. The powder was compacted using a hydraulic press with a pressure of 5 tons to obtain a pre-assembled composite sheet.
[0090] (4) Place the pre-assembled composite sheet into a vacuum furnace and heat it for 10 -4 The purified and shaped composite sheet was obtained by heating at 600°C in vacuum and keeping the temperature for 2 hours.
[0091] (5) The purified and shaped composite sheet was matched with a conventional suitable carbon salt tube and pyrophyllite block, and subjected to high temperature and high pressure treatment in a six-sided top press, with a pressure of 5.5 GPa, a temperature of 1750°C, and a heat preservation and pressure holding time of 18 minutes to obtain a nano-diamond composite sheet with no cracks in appearance.
[0092] The wear ratio of the obtained nano-diamond composite sheet was tested using "JB / T 3235-2013: Determination of Wear Ratio of Polycrystalline Diamond". The wear ratio of the nano-diamond composite sheet obtained by the silicon carbide grinding wheel test was 1.5×10 4 .
[0093] The impact toughness of the obtained nano-diamond composite sheet was tested using an impact toughness testing machine. The nano-diamond composite sheet was processed by electric spark wire cutting into a sample with a diameter of 13.8 mm. The weight height was 13.5 cm, the weight was 0.6 kg, the single impact energy was 0.7938 J, and after 30 continuous impacts, the edge damage length was 1.75 mm, showing a dimple fracture.
[0094] Example 5
[0095] (1) 94.0 g of 200 nm diamond powder, 1.0 g of 100 nm cubic boron nitride, 1.5 g of 1-100 nm tungsten carbide, 0.2 g of 3-10 layers of graphene, 2.0 g of 100 nm cobalt powder, 0.8 g of 200 nm tantalum powder, and 0.4 g of 1-100 nm vanadium powder were ball-milled in a stainless steel tank containing an organic solvent at a rate of 120 r / min for 6 hours. The mixture was dried at 80° C. and sieved through a 100-mesh sieve to obtain a mixed powder.
[0096] (2) The mixed micropowder is reduced in hydrogen at 500° C. for 2 h with a hydrogen pressure of 0.08 MPa to obtain reduced mixed micropowder.
[0097] (3) 3.5 g of reduced mixed micro powder was spread evenly into a niobium cup with a diameter of 35 mm and covered with a 3 mm thick cemented carbide (grade YG16). A suitable molybdenum cup was matched as a lid. The powder was compacted using a hydraulic press with a pressure of 5 tons to obtain a pre-assembled composite sheet.
[0098] (4) Place the pre-assembled composite sheet into a vacuum furnace and heat it for 10 -4 The purified and shaped composite sheet was obtained by heating at 600°C in vacuum and keeping the temperature for 2 hours.
[0099] (5) The purified and shaped composite sheet is matched with a conventional suitable carbon salt tube and pyrophyllite block, and subjected to high temperature and high pressure treatment in a six-sided top press, with a pressure of 6.0 GPa, a temperature of 1600°C, and a heat preservation and pressure holding time of 18 minutes to obtain a nano-diamond composite sheet with no cracks in appearance.
[0100] The wear ratio of the obtained nano-diamond composite sheet was tested using "JB / T 3235-2013: Determination of Wear Ratio of Polycrystalline Diamond". The wear ratio of the nano-diamond composite sheet obtained by the silicon carbide grinding wheel test was 1.7×10 4 .
[0101] The impact toughness of the obtained nano-diamond composite sheet was tested using an impact toughness testing machine. The nano-diamond composite sheet was processed by electric spark wire cutting into a sample with a diameter of 13.8 mm. The weight height was 13.5 cm, the weight was 0.6 kg, the single impact energy was 0.7938 J, and after 30 continuous impacts, the edge damage length was 1.66 mm, showing a dimple fracture.
[0102] Comparative Example 1
[0103] (1) 94.0 g of 200 nm diamond powder, 5.0 g of 100 nm cobalt powder, 0.8 g of 200 nm tantalum powder, and 0.4 g of 0-100 nm vanadium powder were ball-milled in a stainless steel tank containing an organic solvent at a rate of 120 r / min for 6 hours. The mixture was dried at 80° C. and sieved through a 100-mesh sieve to obtain a mixed powder.
[0104] (2) The mixed micropowder is reduced in hydrogen at 500° C. for 2 h with a hydrogen pressure of 0.08 MPa to obtain reduced mixed micropowder.
[0105] (3) 3.5 g of reduced mixed micro powder was spread evenly into a niobium cup with a diameter of 35 mm and covered with a 3 mm thick cemented carbide (grade YG16). A suitable molybdenum cup was matched as a lid. The powder was compacted using a hydraulic press with a pressure of 5 tons to obtain a pre-assembled composite sheet.
[0106] (4) Place the pre-assembled composite sheet into a vacuum furnace and heat it for 10 -4 The purified and shaped composite sheet was obtained by heating at 600°C in vacuum and keeping the temperature for 2 hours.
[0107] (5) The purified and shaped composite sheet was matched with a conventional suitable carbon salt tube and pyrophyllite block, and subjected to high temperature and high pressure treatment in a six-sided top press, with a pressure of 6.0 GPa, a temperature of 1750° C., and a heat preservation and pressure holding time of 18 min. The polycrystalline layer of the obtained nano-diamond composite sheet had cracks in appearance.
[0108] The wear ratio of the obtained nano-diamond composite sheet was tested using "JB / T 3235-2013: Determination of wear ratio of polycrystalline diamond". The wear ratio of the nano-diamond composite sheet obtained by the silicon carbide grinding wheel test was 1.8×10 4 .
[0109] The impact toughness of the obtained nano-diamond composite sheet was tested using an impact toughness testing machine. The nano-diamond composite sheet was processed by electric spark wire cutting into a sample with a diameter of 13.8 mm. The weight height was 13.5 cm, the weight was 0.6 kg, the single impact energy was 0.7938 J, and after 30 continuous impacts, the edge damage length was 2.37 mm, showing a dimple fracture.
[0110] Comparative Example 2
[0111] (1) 94.0 g of 200 nm diamond powder, 1.5 g of 1-100 nm tungsten carbide, 0.2 g of 3-10 layers of graphene, 2.0 g of 100 nm cobalt powder, 0.8 g of 200 nm tantalum powder, and 0.4 g of 1-100 nm vanadium powder were ball-milled in a stainless steel tank containing an organic solvent at a rate of 120 r / min for 6 hours. The mixture was dried at 80° C. and sieved through a 100-mesh sieve to obtain a mixed powder.
[0112] (2) The mixed micropowder is reduced in hydrogen at 500° C. for 2 h with a hydrogen pressure of 0.08 MPa to obtain reduced mixed micropowder.
[0113] (3) 3.5 g of reduced mixed micro powder was spread evenly into a niobium cup with a diameter of 35 mm and covered with a 3 mm thick cemented carbide (grade YG16). A suitable molybdenum cup was matched as a lid. The powder was compacted using a hydraulic press with a pressure of 5 tons to obtain a pre-assembled composite sheet.
[0114] (4) Place the pre-assembled composite sheet into a vacuum furnace and heat it for 10 -4 The purified and shaped composite sheet was obtained by heating at 600°C in vacuum and keeping the temperature for 2 hours.
[0115] (5) The purified and shaped composite sheet was matched with a conventional suitable carbon salt tube and pyrophyllite block, and subjected to high temperature and high pressure treatment in a six-sided top press with a pressure of 6.0 GPa, a temperature of 1750°C, and a heat preservation and pressure holding time of 18 min. The polycrystalline layer of the obtained nano-diamond composite sheet had obvious cracks in appearance.
[0116] The wear ratio of the obtained nano-diamond composite sheet was tested using "JB / T 3235-2013: Determination of wear ratio of polycrystalline diamond". The wear ratio of the nano-diamond composite sheet obtained by the silicon carbide grinding wheel test was 1.8×10 4 .
[0117] The impact toughness of the obtained nano-diamond composite sheet was tested using an impact toughness testing machine. The nano-diamond composite sheet was processed by electric spark wire cutting into a sample with a diameter of 13.8 mm. The weight height was 13.5 cm, the weight was 0.6 kg, the single impact energy was 0.7938 J, and after 30 continuous impacts, the edge damage length was 2.36 mm, showing a dimple fracture.
[0118] Comparative Example 3
[0119] (1) 94.0 g of 200 nm diamond powder, 2.0 g of 100 nm cubic boron nitride, 0.2 g of 3-10 layers of graphene, 2.0 g of 100 nm cobalt powder, 0.8 g of 200 nm tantalum powder, and 0.4 g of 1-100 nm vanadium powder were ball-milled in a stainless steel tank containing an organic solvent at a rate of 120 r / min for 6 hours. The mixture was dried at 80° C. and sieved through a 100-mesh sieve to obtain a mixed powder.
[0120] (2) The mixed micropowder is reduced in hydrogen at 500° C. for 2 h with a hydrogen pressure of 0.08 MPa to obtain reduced mixed micropowder.
[0121] (3) 3.5 g of reduced mixed micro powder was spread evenly into a niobium cup with a diameter of 35 mm and covered with a 3 mm thick cemented carbide (grade YG16). A suitable molybdenum cup was matched as a lid. The powder was compacted using a hydraulic press with a pressure of 5 tons to obtain a pre-assembled composite sheet.
[0122] (4) Place the pre-assembled composite sheet into a vacuum furnace and heat it for 10 -4The purified and shaped composite sheet was obtained by heating at 600°C in vacuum and keeping the temperature for 2 hours.
[0123] (5) The purified and shaped composite sheet was matched with a conventional suitable carbon salt tube and pyrophyllite block, and subjected to high temperature and high pressure treatment in a six-sided top press with a pressure of 6.0 GPa, a temperature of 1750°C, and a heat preservation and pressure holding time of 18 min. The polycrystalline layer of the obtained nano-diamond composite sheet had obvious cracks in appearance.
[0124] The wear ratio of the obtained nano-diamond composite sheet was tested using "JB / T 3235-2013: Determination of Wear Ratio of Polycrystalline Diamond". The wear ratio of the nano-diamond composite sheet obtained by the silicon carbide grinding wheel test was 1.7×10 4 .
[0125] The impact toughness of the obtained nano-diamond composite sheet was tested using an impact toughness testing machine. The nano-diamond composite sheet was processed by electric spark wire cutting into a sample with a diameter of 13.8 mm. The weight height was 13.5 cm, the weight was 0.6 kg, the single impact energy was 0.7938 J, and after 30 continuous impacts, the edge damage length was 1.82 mm, showing a dimple fracture.
[0126] Comparative Example 4
[0127] (1) 94.0 g of 200 nm diamond powder, 2.0 g of 100 nm cubic boron nitride, 1.5 g of 1-100 nm tungsten carbide, 2.0 g of 100 nm cobalt powder, 0.8 g of 200 nm tantalum powder, and 0.4 g of 1-100 nm vanadium powder were ball-milled in a stainless steel tank containing an organic solvent at a rate of 120 r / min for 6 hours. The mixture was dried at 80° C. and sieved through a 100-mesh sieve to obtain a mixed powder.
[0128] (2) The mixed micropowder is reduced in hydrogen at 500° C. for 2 h with a hydrogen pressure of 0.08 MPa to obtain reduced mixed micropowder.
[0129] (3) 3.5 g of reduced mixed micro powder was spread evenly into a niobium cup with a diameter of 35 mm and covered with a 3 mm thick cemented carbide (grade YG16). A suitable molybdenum cup was matched as a lid. The powder was compacted using a hydraulic press with a pressure of 5 tons to obtain a pre-assembled composite sheet.
[0130] (4) Place the pre-assembled composite sheet into a vacuum furnace and heat it for 10 -4 The purified and shaped composite sheet was obtained by heating at 600°C in vacuum and keeping the temperature for 2 hours.
[0131] (5) The purified and shaped composite sheet was matched with a conventional suitable carbon salt tube and pyrophyllite block, and subjected to high temperature and high pressure treatment in a six-sided top press with a pressure of 6.0 GPa, a temperature of 1750°C, and a heat preservation and pressure holding time of 18 min. 50% of the samples of the obtained nano-diamond composite sheet had obvious cracks in the appearance of the polycrystalline layer.
[0132] The wear ratio of the obtained nano-diamond composite sheet was tested using "JB / T 3235-2013: Determination of Wear Ratio of Polycrystalline Diamond". The wear ratio of the nano-diamond composite sheet obtained by the silicon carbide grinding wheel test was 1.7×10 4 .
[0133] The impact toughness of the obtained nano-diamond composite sheet was tested using an impact toughness testing machine. The nano-diamond composite sheet was processed by electric spark wire cutting into a sample with a diameter of 13.8 mm. The weight height was 13.5 cm, the weight was 0.6 kg, the single impact energy was 0.7938 J, and after 30 continuous impacts, the edge damage length was 1.96 mm, showing a dimple fracture.
[0134] Comparative Example 5
[0135] (1) 93.0 g of 200 nm diamond powder, 2.0 g of 100 nm cubic boron nitride, 1.5 g of 1-100 nm tungsten carbide, 0.2 g of 3-10 layers of graphene, 2.0 g of 100 nm cobalt powder, 0.8 g of 200 nm tantalum powder, and 0.4 g of 1-100 nm vanadium powder were ball-milled in a stainless steel tank containing an organic solvent at a rate of 120 r / min for 6 hours. The mixture was dried at 80° C. and sieved through a 100-mesh sieve to obtain a mixed powder.
[0136] (2) The mixed micropowder is reduced in hydrogen at 500° C. for 2 h with a hydrogen pressure of 0.08 MPa to obtain reduced mixed micropowder.
[0137] (3) 3.5 g of reduced mixed micro powder was spread evenly into a niobium cup with a diameter of 35 mm and covered with a 3 mm thick cemented carbide (grade YG16). A suitable molybdenum cup was matched as a lid. The powder was compacted using a hydraulic press with a pressure of 5 tons to obtain a pre-assembled composite sheet.
[0138] (4) Place the pre-assembled composite sheet into a vacuum furnace and heat it for 10 -4 The purified and shaped composite sheet was obtained by heating at 600°C in vacuum and keeping the temperature for 2 hours.
[0139] (5) The purified and shaped composite sheet was matched with a conventional suitable carbon salt tube and pyrophyllite block, and subjected to high temperature and high pressure treatment in a six-sided top press with a pressure of 4.5 GPa, a temperature of 1750°C, and a heat preservation and pressure holding time of 18 min. The obtained nano-diamond composite sheet had obvious cracks in appearance, most areas of the surface of the polycrystalline layer were graphitized and blackened, and most of the polycrystalline layers of the composite sheets were delaminated.
[0140] The samples without delamination were selected and the wear ratio of the obtained nano-diamond composite sheet was tested using "JB / T 3235-2013: Determination Method of Wear Ratio of Polycrystalline Diamond". The wear ratio of the nano-diamond composite sheet obtained by the silicon carbide grinding wheel test was 1.2×10 4 .
[0141] The impact toughness of the obtained nano-diamond composite sheet was tested using an impact toughness testing machine. The nano-diamond composite sheet was processed by electric spark wire cutting into a sample with a diameter of 13.8 mm. The weight height was 13.5 cm, the weight was 0.6 kg, the single impact energy was 0.7938 J, and after 30 continuous impacts, the edge damage length was 3.61 mm, showing a dimple fracture.
[0142] Comparative Example 6
[0143] (1) 93.0 g of 200 nm diamond powder, 2.0 g of 100 nm cubic boron nitride, 1.5 g of 1-100 nm tungsten carbide, 0.2 g of 3-10 layers of graphene, 2.0 g of 100 nm cobalt powder, 0.8 g of 200 nm tantalum powder, and 0.4 g of 1-100 nm vanadium powder were ball-milled in a stainless steel tank containing an organic solvent at a rate of 120 r / min for 6 hours. The mixture was dried at 80° C. and sieved through a 100-mesh sieve to obtain a mixed powder.
[0144] (2) The mixed micropowder is reduced in hydrogen at 500° C. for 2 h with a hydrogen pressure of 0.08 MPa to obtain reduced mixed micropowder.
[0145] (3) 3.5 g of reduced mixed micro powder was spread evenly into a niobium cup with a diameter of 35 mm and covered with a 3 mm thick cemented carbide (grade YG16). A suitable molybdenum cup was matched as a lid. The powder was compacted using a hydraulic press with a pressure of 5 tons to obtain a pre-assembled composite sheet.
[0146] (4) Place the pre-assembled composite sheet into a vacuum furnace and heat it for 10 -4 The purified and shaped composite sheet was obtained by heating at 600°C in vacuum and keeping the temperature for 2 hours.
[0147] (5) The purified and shaped composite sheet is matched with a conventional suitable carbon salt tube and pyrophyllite block, and subjected to high temperature and high pressure treatment in a six-sided top press with a pressure of 6.0 GPa, a temperature of 1500° C., and a heat preservation and pressure holding time of 18 min to obtain a nano-diamond composite sheet.
[0148] The wear ratio of the obtained nano-diamond composite sheet was tested using "JB / T 3235-2013: Determination of Wear Ratio of Polycrystalline Diamond". The wear ratio of the nano-diamond composite sheet obtained by the silicon carbide grinding wheel test was 1.7×10 4 .
[0149] The impact toughness of the obtained nano-diamond composite sheet was tested using an impact toughness testing machine. The nano-diamond composite sheet was processed by electric spark wire cutting into a sample with a diameter of 13.8 mm. The weight height was 13.5 cm, the weight was 0.6 kg, the single impact energy was 0.7938 J, and after 30 continuous impacts, the edge damage length was 1.79 mm, showing a dimple fracture.
[0150] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A nano-diamond composite sheet, comprising a cemented carbide substrate and a superhard material hot-pressed on the surface of the cemented carbide substrate, wherein the superhard material is prepared from raw materials comprising the following mass percentages:
2. The nano-diamond composite sheet according to claim 1, characterized in that: The particle size of the diamond powder is 1 to 200 nm; The diameter of the cubic boron nitride sheet is 1 to 100 nm; The particle size of the tungsten carbide is 1 to 100 nm; The particle size of the cobalt powder is 1 to 100 nm; The particle size of the tantalum powder is 1 to 100 nm; The particle size of the vanadium powder is 1-100 nm.
3. The nano-diamond composite sheet according to claim 1, characterized in that: The graphene is one or more of single-layer graphene, multi-layer graphene and graphene-like.
4. The method for preparing the nano-diamond composite sheet according to any one of claims 1 to 3, comprising the following steps: Diamond micropowder, cubic boron nitride, tungsten carbide, cobalt powder, tantalum powder, vanadium powder and graphene are ball-milled and mixed to obtain mixed micropowder; placing the mixed micropowder in a hydrogen atmosphere to perform a reduction reaction to obtain reduced mixed micropowder; Pressing the cemented carbide sheet and the reduced mixed micro powder into a pre-assembled composite sheet; Under vacuum conditions, the pre-assembled composite sheet is heated, purified and shaped to obtain a purified and shaped composite sheet; The purified and shaped composite sheet is subjected to high temperature and high pressure treatment to obtain a nano-diamond composite sheet.
5. The preparation method according to claim 4, characterized in that: The ball milling mixing speed is 120-180 r / min, and the time is 3-9 h.
6. The preparation method according to claim 4, characterized in that: The temperature of the reduction reaction is 350-950° C., and the time is 0.5-3 h; the pressure of hydrogen in the hydrogen atmosphere is 0.02-0.1 MPa.
7. The preparation method according to claim 4 or 6, characterized in that: The pressing pressure is 3 to 5 tons and the pressing time is 3 to 30 seconds.
8. The preparation method according to claim 4, characterized in that: The temperature of the heating, purification and shaping is 600-1100°C, and the insulation time is 1-3h; The vacuum degree of the vacuum condition is 10 -2 ~10 -4 Pa.
9. The preparation method according to claim 4 or 8, characterized in that: The temperature of the high temperature and high pressure treatment is 1600-1900° C., the pressure is 5-6.5 GPa, and the heat and pressure holding time is 12-25 minutes.
10. Use of the nano-diamond composite sheet according to any one of claims 1 to 3 or the nano-diamond composite sheet according to any one of claims 4 to 9 in a cutting tool.
Citation Information
Patent Citations
Preparation method of carbon nanotube reinforced diamond composite material
CN102268619A
Graphene-containing diamond composite sheet and preparation method thereof
CN110253024A
High-performance grinding wheel for titanium alloy cutting and preparation method of high-performance grinding wheel
CN115592577A
Composite structures for energy dissipation and method
US20230288173A1
Method for manufacturing polycrystalline diamond compact enhanced by CVD diamond
WO2013185511A1